Reduced graphene oxide-based calcium alginate hydrogel as highly efficient solar steam generation membrane for desalination - LOU, Gang; WANG, Yizhi; MA, Yun; KOU, Jianlong; WU, Fengmin; FAN, Jintu (Frontiers of materials science, 2021)
Solar-driven evaporation has been considered as one of the potential methods for desalination and sewage treatment. However, optical concentrators and complex multi-component systems are essential in advanced technologies, resulting in low efficiency and high cost. Here, we synthesize a reduced graphene oxide-based porous calcium alginate (CA-rGO) hydrogel which exhibits good performance in light absorption. More than 90% of the light in the whole spectrum can be absorbed. Meanwhile, the water vapor escapes from the CA-rGO film extremely fast. The water evaporation rate is 1.47 kg·m −2·h −1, corresponding to the efficiency 77% under only 1 kW·m −2 irradiation. The high evaporation efficiency is attributed to the distinctive structure of the film, which contains inherent porous structure of hydrogel enabling rapid water transport throughout the film, and the concave water surfaces formed in the hydrophilic pores provide a large surface area for evaporation. Hydrophobic rGO divides the evaporation surface and provides a longer three-phase evaporation line. The test on multiple cyclic radiation shows that the material has good stability. The CA-rGO hydrogel may have promising application as a membrane for solar steam generation in desalination and sewage treatment.